THE IMAGE A VISUALLY IMPAIRED PERSON IN PHILATELY AS A MEANS OF FORMING AN ADEQUATE ATTITUDE TOWARDS THE BLINDNESS AND BLIND - Gudonis, Vytautas (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The topic of blindness and the image of a blind person in philately, although rarely analysed, has a great information potential. This research topic is part of our research "The Image of a Blind Man in the Cultural Heritage of Humanity." The purpose of the study is to systematize knowledge on the subject of image and blindness in philately, to consider the social aspects of this phenomenon. To collect information, the bulletin used the analysis of literature and the search for postage stamps depicting blind people in private collections of philatelists. The iconological method of interpretation of culture and art history was also used, which permitted to reveal the meaning of visions, symbols and their contexts. The monograph is based on the methodological assumptions of art historians Aby Walburg (1866 – 1929) and Erwin Panofsky (1892 – 1968), who claimed that historical and social aspects could be revealed through the works of art. E. Panofsky states that the works of art as human signs as well as other works can be considered documents, encoding the knowledge of the epoch, its culture and attitudes. The work of art is a symbol, indicating “something else” and allowing us to perceive the allegory; it is a document, telling us about certain cultural, religious, social and historic phenomena, depending on the context. The image of a blind person in stamps and commemorative envelopes are divided according to separate themes and analysed as social phenomena. The image of the blind and the topic of blindness in philately allow acquiring more knowledge about the blind, their potential, embossed writing, specificity of their orientation and mobility and at the same time forming positive attitudes towards visually impaired people. These findings activate further research on the image of a blind person in other areas of cultural heritage.